PENTINGNYA PENDIDIKAN PERBANKAN UNTUK MENGATASI KELANGKAAN MODAL DALAM UMKM - Setiadi Umar (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
According to the Ministry of Trade and Industry of the Republic of Indonesia (Deperindag), there are problems faced by Small Medium Enterprise(s) (SMEs) to develop themselves. Some of these problems are the insufficiency capital, limited knowledge, uncompetitive financing schemes and lack of education of the SME's owners aggravating the problem. This paper discusses the condition of Indonesian banking and other financial institutions as well as capital conditions, the condition of SME(s,) and the needs of financial and business education for SMEs. Finally, this paper suggests alternative solutions to the problem.Keywords: Small Medium Enterprises (SME)s, SMEs development, SMEs Business Education, Indonesian Banks and LDR, private sector development.